Making sense of coaching - e uthor; Sage eBooks (Los Angeles : SAGE, 2014)
This title examines the process of coaching rather than its techniques and goals, addressing issues such as the problematic relationship between coach and coachee in business coaching when the explicit goal is to improve individual performance within an organisation.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Employees -- Coaching of; Electronic books